Dampak Perilaku Fanatisme Game Online Terhadap Minat Membaca Al-Quran pada Siswa Sekolah Dasar - Andri Yuningsih; Mahmudi (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
Online games have a sizable market in Indonesia. In recent years, the proliferation of online games has been quite rapid. One of the consequences of playing online games is addiction. Playing online games significantly impacts a child's daily activities, including social interactions, learning, and religious activities, leading to a decline in religious interests such as reciting the Qur'an or reading it because of the time spent